Metallic Axe Causing Cranial Injury: A Case Report - Yadav, Dipak Kumar; Sheikh, Sadaf Saleem (Eastern Green Neurosurgery, 2020)
Axe as the weapon holds features of both sharp and blunt forces. Physical assault in our community is generally noticed but with such unique weapon is not frequently heard. Homicidal inflicting injury to the head is common in physical assault. Many cases are being admitted with a history of head injury with blunt objects and sharp objects but very few cases are being documented in literature about the use of axe as a weapon. Here is presented a case of 46-year-old right handed male patient form a village in Siraha was brought to the emergency department with the history of physical assault with sharp edged metallic axe.